Moral Luck and the Problem of the Innocent Attacker. (16th April 2014) - Statman, Daniel
Abstract The purpose of this paper is to explore the relation between the right to self‐defense against an innocent attacker and the notion of moral luck. It argues that those who accept the existence of such a right rely on the assumption that mere agency makes a significant moral difference – which is precisely the assumption that underlies the view held by believers in moral luck. Those who believe in the right to self‐defense against innocent attackers are thus committed to the idea of moral luck much more than they usually acknowledge. The paper also argues that the arguments offered in support of moral luck, in particular the one based on the relation between agency and self‐identity, might help to shed light on the rather puzzling above right.